"Building bonds: Key drivers of patient loyalty in healthcare": A mini-review: Patient loyalty - Sarkis, Elianor; Nehme, Maha (Technium Sustainability, 2025)
Introduction: The hospital environment is characterized by increased competition, accelerated development of medical technologies, greater complexity and technicality of care, as well as increased patient demands. To meet these demands, hospitals must provide quality care that meets patients' needs and expectations. They must also develop long-term relationships with their patients to create a bond of trust and loyalty. Objective: This work aims to synthesize the factors affecting patient loyalty in hospitals and to identify possible areas for improvement. Results: The determinants of a patient’s loyalty in a hospital start with the management approach and patient satisfaction, the service quality and the brand image of the hospital, and include hospitality services, visibility of the hospital, communication and confidentiality, reputation and availability of doctors, nursing care, and leadership and the relationships between doctors, nurses, and patients. In addition to health care services that comprise administrative procedures and support programs for patients and families, artificial intelligence and diagnostic platforms have been highlighted as principal factors affecting patient loyalty and trust. Marketing in the healthcare sector can affect patient trust, and demographic and psychosocial profiles of patients also influence patient loyalty. Each factor can affect patient loyalty in a hospital to a specific degree. Although classic patient loyalty programs exist in some hospitals, inspired by other sectors, they are part of rather patient retention strategies and lack specificity and connection to factors influencing loyalty behavior. Conclusion: Measurement and analysis of the impact of determinants of patient loyalty in hospitals improves the performance of healthcare providers and hospital profitability.